PEMBERDAYAAN MASYARAKAT PADA MASA COVID-19 - Nurharisyah Hasibuan; Sarwan Sarwan (UIN Imam Bonjol Padang, 2021)
This study aims to determine community empowerment during the Covid-19 period through recitation programs, both community empowerment in the intellectual, economic and health fields. This research is a field research with a descriptive method approach that is in accordance with field phenomenology. The theory used is the concept of community empowerment from M Quraish Shihab. The results showed that intellectual, economic and public health empowerment did not work as expected by Takmir Masjid as was the case before the Covid-19 pandemic. The recitation program seeks to improve the welfare of the community in the intellectual, economic and health fields. The impact of this research is expected to provide scientific contributions in improving the welfare of the community.